Qualitative evaluation of the general practitioner chronic non-communicable diseases training programme - Zhang, Chunyu (BMC Med Educ, 2020)
BACKGROUND: In China, general practitioners have limited ability to provide care for common chronic non-communicable diseases because they lack postgraduate training. In an attempt to improve general practitioners’ skills in this regard, the present authors previously launched the Chronic Non-Communicable Diseases Training Programme. The present study aims to evaluate the effectiveness of this programme. METHODS: Thirty-nine trainee general practitioners who participated in the programme underwent semi-structured interviews, which explored how they performed the training, what they achieved from the programme, and their suggestions for future programmes. The interview data were analysed using a thematic analysis approach. RESULTS: Under the guidance of supervisors, the thirty-nine trainee general practitioners completed the structured but individualised training plan, which comprised a four-day basic theory class, 3 months practising in a ward, and 6 months assisting in an outpatient clinic. They reported an improvement in their ability to provide care for chronic non-communicable diseases and perform two-way referral, as well as their communication with patients. They also reported that, since returning to their communities, they had become more confident, were building better relationships with their patients, and had changed their clinic behaviours from copying prescriptions to making medical decisions independently. Their principal suggestion for the training programme was to alter the order of the training, as they preferred to practice in the ward before assisting in the outpatient clinic. CONCLUSION: The course comprised a learner-centred, practice- and apprenticeship-based, general-practitioner training programme. Given the participants’ progress and the beneficial effects of the programme reported in the interview data, it appears to be worthwhile to extend the General Practitioner Chronic Non-Communicable Diseases Training Programme.